Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Literasi Numerasi Siswa Kelas V UPTD SDN Tanjungbumi 3 - Siti Nurrohmah; Isna Ida Mardiyana (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the effect of a realistic mathematics education (RME) approach on students' numeracy literacy skills. This study used the One-Group Pretest-Posttest Design. The sample used in this study used a saturated sampling technique with a total sample of 31 students. Collecting research data using observation, tests, and documentation. The results of this study indicate that the realistic mathematics education (RME) approach has an effect on the numeracy literacy abilities of grade 5 Elementary School of Tanjungbumi 3 Bangkalan Regency. Based on the calculation of the hypothesis test with the paired sample t-test obtained t_test > t_table of 20.769 then is accepted and is rejected and a significance value of 0.000 <0.05 then is rejected and is accepted, which means that there is a significant influence on the use of the approach realistic mathematics education (RME) on numeracy literacy skills. The implementation of learning is carried out with very good criteria with an average of 86.5.